New Brightener for Zn-Fe Alloy Plating from Sulphate Bath - B. M. Praveen; T. V. Venkatesha (International Journal of Electrochemistry)
Zn-Fe alloy electrodeposition was carried out in the presence of condensation product 2-{[(1E)-(3,4-dimethoxyphenyl)methylidene]amino}-3-hydroxypropanoic acid formed between veratraldehyde and serine in acid sulphate bath. Hull cell was used for optimizing the operating parameters and bath constituents. During deposition, the potential was shifted towards cathodic direction in the presence of addition agents and brightener. The polarization studies show that deposition taking place in basic bath and optimum bath was 1.08 and 1.15 V, respectively. Current efficiency and throwing power were reached around 85% and 26%, respectively. The SEM images of bright deposit indicated its fine-grained nature and appreciable reduction in the grain size. XRD studies have showed that the grain size of the deposit generated from optimum bath was 16 nm. UV-visible spectroscopic studies confirm the formation of complex between metal ion and brightener.